The burden of poisoning in children hospitalised at a tertiary-level hospital in South Africa - Mahtaab Khan; Fatima Solomon; Alane Izu; Pepukai Bengura; Grace Okudo; Basetsana Maroane; Nilesh Lala; Ziyaad Dangor; Ziyaad Dangor (Frontiers Media S.A., 2023)
IntroductionGlobally, childhood poisoning, accounts for a significant proportion of emergency department admissions. There is a paucity of data from low- and middle-income countries on poisoning in children.ObjectiveTo describe the incidence, case fatality rate, and types of poisoning in children admitted to a tertiary-level hospital in Johannesburg, South Africa.MethodsThis was a retrospective descriptive study of children hospitalised with poisoning from January 2016 to December 2021 at Chris Hani Baragwanath Academic Hospital. Children were identified from a discharge summary database using ICD-10 codes that describe poisoning. Trends in incidence of poison exposure were reported.ResultsOf the 60,901 admissions during the study period, 2,652 (4.4%) children were diagnosed with poisoning. Most (71.3%) children were less than 5 years of age and 55% were male. The incidence of poisoning per 100,000 was highest at 108.4 (95% CI: 104.3-112.6) in 2019 and decreased to 77.3 (95% CI: 73.9-80.7) in 2020 and 59.6 (95% CI: 56.3-62.5) in 2021. Main causes of poisoning were organic solvents (37.6%), medications (32.9%), and pesticides (17.5%). The overall case fatality rate was 2.1%. In a multivariate analysis, poisoning secondary to pesticides (aOR: 13.9; 95% CI: 4.52-60.8; p < 0.001), and unspecified agents (aOR: 12.7; 95% CI: 3.27-62.8; p < 0.001) were associated with an increased odds of death.ConclusionWe report a high prevalence of poisoning in children hospitalised in this tertiary-level hospital in South Africa. Public health measures to reduce the burden of organic solvents, medications and pesticide poisoning are urgently warranted.